The evolution of the European Stability Mechanism: Lessons for Asian integration - Frank Rövekamp (Asian Development Bank Institute (ADBI), 2020)
The European Stability Mechanism (ESM) is a permanent institution with the purpose of providing financial stability to the 19 countries in the eurozone. It was founded in 2012 at the height of the sovereign debt crisis in Europe. Originally, the European Union and the eurozone intended to operate without a regional financial stability mechanism. However, the severity of the crisis forced the abolishment of the principal of complete fiscal self-reliance for each member country. During the course of the crisis, the ESM and other organizations provided financial assistance to the crisis countries - Greece, Ireland, Portugal, Spain, and Cyprus-amounting to exteuro400 billion. This may have helped to contain the crisis, but the regional financial stability arrangement in Europe has suffered from organizational and procedural over-complexity. Reforming the system is proving difficult because of disunity among eurozone members. The regional financial stability mechanism in Asia, the Chiang Mai Initiative, was created after the Asian crisis of 1997/98 and could therefore be developed without immediate pressure. There are signs that it lacks effectiveness, however, because of an insufficient funding base and a lack of capabilities to provide reform programs and surveillance for crisis countries. Here, the experiences in Europe can provide hints for a way ahead in Asia: committed funding should match the needs of a potential crisis. Furthermore, organizational capabilities need to be enhanced, but without creating undue complexities in decision-making and institutional setup.
Keywords: F3; H6; 330; European Stability Mechanism; regional financial stability; sovereign debt crisis; Chiang Mai Initiative